MODEL SISTEM DINAMIS PENILAIAN KINERJA AGROINDUSTRI TEMBAKAU DI PT GADING MAS INDONESIA TOBACCO - M. Amirul Ghifarri; Bambang Herry Purnomo; Noer Novijanto (Faculty of Agricultural Technology, University of Jember, 2016)
Performance is a very important aspect the survival of a company. Optimalize performance of a company is the key of existence. Gading Mas Indonesia Tobacco (GMIT) company is one of the companies in Jemer Regency that export Besuki Na-Oogst tobacco leaf to many countries. One effort, GMIT company to increase competitiveness is assessing performance. To improve its performance, GMIT company declareobjectives in the Work Plant and Budget Based of result in 2014, value of benefict and rendemen has not been reached. This condition requies the evaluation of the performance assessment approach that can improve performance of the company. The aim of this research is build a system dynamic model for performance assesment in GMIT company. The method used in this research is dynamic system method. The approach with this method can determine the behavior of importance variables that change ver time. Simulations done by creating a model based on company’s success area and start in 2015 until 2021. Model was developed by simulatting in several scenarios alternative, optimistic, moderate and pessimistic. Based on the result of data analysis known that the best policy scenario is an optimistic scenario. Optimistic scenario has an average value of dekom production 1463.3 quintals above the basic scenario of 1247.8 quintals per year. The average value of the highest profit of Rp. 4.856.431.700 above the average value of the basic scenario profit of Rp. 4.583.563.100. The average value of the highest employee capabilities with 8.21 point above the base scenario with a value of 6 points.Keywords: performance, PT. GMIT, system dynamic